Renewing focus on family planning service quality globally. Issue 1 (December 2016) - Hancock, Nancy; Stuart, Gretchen; Tang, Jennifer; Chibwesha, Carla; Stringer, Jeffrey; Chi, Benjamin
Abstract Reducing the global unmet need for contraception is currently a priority for many governments, multi-lateral initiatives, non-governmental organizations, and donors. Evidence strongly suggests that the provision of quality family planning services can increase uptake, prevalence, and continuation of contraception. While an accepted framework to define the components of family planning service quality exists, translating this framework into assessment tools that are accessible, easily utilized, and valid for service providers has remained a challenge. We propose new approaches to improve the standardization and accessibility of family planning service quality assessment tools to simplify family planning service quality evaluation. With easier approaches to program evaluation, quality improvements can be performed more swiftly to help increase uptake and continuation of contraception to improve the health of women and their families.